Technology Entrepreneurship Project (ENT 600) : Hunan Rika Tech. Co Ltd / Hanies Ardeenie Mohd Azman - Mohd Azman, Hanies Ardeenie (2022)
This subject is an attempt for student to know how to understand and study the business theory of a certain company that can be put into practical situation. Hence as for me I was giving an opportunity to study on the business theory and rules which run a sensor manufacturer product which is Hunan Rika tech.co Ltd company based in China In the first section, I need to study on the purpose of this case study and the problem statement faced by this company. Next section, I was giving a task to study on their company background and choose a product from their company and figure out on how the product works in term of technology parts. Plus, I also collect the information on how Hunan Rika dealing and manage their business strategy in achieving their business goals and perform an effective management. Most information I collected from their company’s website and few secondary sources as well to supports all the facts. In this case study, I analysed the strength, weakness, opportunities and threats of this company in real business using SWOT analysis. Thus, in the last section I was given to came out with few solution that can overcome or improve the need and demand from consumers.